A Three-Dimensional Study on the Microstructure of Achilles Tendons - Pang, Xin (Curtin University, 2017)
Utilising confocal and second harmonic generation microscopy, this PhD project developed a 3D imaging technique and studied the cell morphology and microstructure of the collagen fibrils and elastic fibres of healthy rabbit Achilles tendons from the mid-portion to enthesis. Computer imaging analysis techniques have also been developed in this study to quantitatively characterise the cell morphology and microstructure of the collagen and elastic fibrillar network.